Application of Monodisperse Encapsulated Phase Change Materials in Building Thermal Energy Storage - Li, Zhenya; Liu, Chuanliang; Chen, Yingying; Hao, Ning; Jiang, Li; Bian, Wenjie (Frontiers in Energy Research, 2022)
Monodisperse encapsulated phase change materials (PCMs) are fabricated via microfluidic technology. To evaluate the thermoregulation ability of PCM capsules applied in building thermal energy storage, a gypsum model house with PCM capsules embedded is prepared. The temperature revolutions outside and inside the gypsum model house with different PCM capsules filling ratios are investigated. The effect of the filling ratio of the PCM on the thermoregulation performance is discussed. The potential application of monodisperse encapsulated PCMs in building thermal energy storage is verified. Attributing to the PCM capsules, the thermal response of the gypsum model house to the varying environmental temperature is retarded. As the filling ratios increase, the thermoregulation performance of the gypsum model house is better.